Lived experiences of migrant and refugee parents: Challenges encountered during their journey and settlement in Europe - Rousou, Elena; Apostolara, Paraskevi; Velonaki, Venetia Sofia; Papadopoulos, Irena; Kalokairinou, Athena; Sakellaraki, Ourania; Dudau, Victor; Kuckert, Andrea; Lazzarino, Runa; Mauceri, Manuela; Pezzella, Alfonso; Kouta, Christiana; et al. (My University, 2025)
Parenting in the context of migration presents a unique set of challenges for refugee parents, who must navigate the cultural norms and expectations of both their home and resettlement countries while balancing their daily parenting responsibilities and practices. This study aims to provide a critical analysis of the experiences, needs, and challenges faced by migrant and refugee parents during their journey and settlement in Europe, as recounted through their personal narratives. Utilizing a qualitative approach, the researchers collected twenty-seven life narratives of migrant and/or refugee parents through purposive sampling. An analysis of the narratives identified four overarching themes that represent the primary challenges faced by refugee families and the need for support. These macro-themes include up rootedness, spatio-temporal uncertainty, trauma and abuses, and parental powerlessness. Parental powerlessness emerged as a synthesis of the causes of trauma from the previous three challenges and highlights the increased loss of parental identity and self-conflict that refugee parents experience. The study reveals that refugee parents face various challenges and barriers, such as language barriers, lack of information and awareness, and cultural differences. It is crucial for healthcare providers and policymakers to consider these findings and develop targeted interventions, such as utilizing interpreters, cultural mediators, and providing culturally sensitive and appropriate healthcare and educational services, as well as implementing specific policies to enhance the health and well-being of refugee parents and their children.
Keywords: Parenting skills; Migrant/refugee family; Cultural Competence; Narratives; Austria